THE STATE OF BRONCHIAL CILIATED EPITHELIUM AND MUCOCILIARY TRANSPORT IN CASE OF CHRONIC BRONCHITIS AND CONCURRENT LONG TERM SMOKING - N. E. Chernekhovskaya; N. Yu. Vyrenkova; I. M. Maltseva; A. V. Volova; A. V. Povalyaev; N. V. Vychuzhanina (Туберкулез и болезни лёгких, 2019)
The objective of the study: to compare the state of mucociliary clearance and bronchial ciliated epithelium in smokers and non-smokers suffering from chronic bronchitis.Subjects and methods. 80 chronic bronchitis patients with exacerbation were examined; they were divided into 2 groups: Group 1 included 40 active smokers and Group 2 comprised of 40 patients who had never smoked. The comparison group included 10 non-smokers with no respiratory disorders. All chronic bronchitis patients had certain examinations including bronchoscopy with biopsy and consequent ultrastructural tests of biopsy specimens and aerosol scintigraphy of the lungs for mucociliary clearance assessment.Results. Morphological and functional changes in the mucociliary transport system were detected in case of chronic bronchitis versus those healthy. Those changes were more profound in the smokers compared to non-smokers. Thus, the smokers with chronic bronchitis were diagnosed with a significant reduction of mucociliary clearance corresponding to degree II of mucociliary transport system failure, which was down to 16.60 ± 2.40% (down to 23.91 ± 2,11% in non-smokers, while it was 34.82 ± 2.14% in health) with concurrent diffuse bilateral bronchitis deformans and significant amount of very viscous mucosal or mucopurulent discharge according to the endoscopy data. The ultrastructural testing of biopsy specimens detected the significant damage of bronchial ciliated epithelium in the form of diffuse atrophy, focal metaplasia, which was one of the obvious causes of significant impairment of mucociliary transport.